Performance of Graphite for Congo Red and Direct Orange Adsorption - Rananda Vinsiah; Risfidian Mohadi; Aldes Lesbani (Indonesian Journal of Environmental Management and Sustainability, 2020)
To investigate its ability, graphite material was characterized by X-Ray diffraction (XRD), Fourier Transform Infrared Spectrophotometer (FTIR), Thermo Gravimetry Differential Thermal Analyse (TG-DTA), and Brunauer Emmet Teller (BET). Adsorption capability was evaluated by using Congo Red dye and Direct Orange dye solutions. The experiment was studied by using kinetic, isotherm, and thermodynamic parameters. The result of XRD characterization showed that graphite has four characteristic peaks which are 26,405?(002), 44,50?(101), 54,45?(004), and 77,32?(006). FT-IR characterization showed that the vibration at 3402 cm-1, 1635 cm-1, and 1381 cm-1. TG-DTA analysis showed that graphite has only one decomposition peak at 760 oC. BET analysis showed that the surface area of graphite was 11,558 m2/g. The optimum pH of CR and DO dyes were in pH 6 and pH 2 with contact time of 120 minutes.  Kinetic adsorption model of CR and DO dye onto graphite follow pseudo-second-order model with a liner regression coefficient close to one. Isotherm parameter of CR and DO adsorption onto graphite follow Langmuir isotherm model with spontaneous endothermic process. The desorption process of graphite was used HCl to remove the dyes.  Regeneration process of graphite showed that the capacity of adsorption decreased after it was reused 3 times.